A description of the male of Geckobiella donnae Paredes-León, Klompen et Pérez, 2012 (Acari: Pterygosomatidae) from captive iguanas in Honduras - Kalúz, Stanislav; Literák, Ivan (Folia parasitologica, 2019)
Mites of the family Pterygosomatidae are usually infesting lizards, geckos and iguanas. In this family, the genus Geckobiella Hirst, 1917 comprises 12 species including Geckobiella donnae Paredes-León, Klompen et Pérez, 2012. We collected 48 mites of G.donnae from 10 captive iguanas Ctenosaura bakeri Stejneger (Reptilia: Iguanidae) out of 23 examined individuals (prevalence 43% ) in Iguana Research and Breeding Station on Isla de Utila, Islas de la Bahía, Honduras on 1 September 2014. Males of G. donnae occurred together with females. The male of G. donnae is described here for the first time. We speculated that G. donnae is autochthonous on Isla de Utila with C. bakeri as a natural host or that it was transmitted to C. bakeri from Iguana iguana (Linnaeus) native to Utila or introduced to Utila from the North American/Central American mainland by a host kept as a pet.
Keywords: roztoči; Honduras; Mite Infestations; Mites; Prevalence; leguáni; Animals; Iguanas; mužské pohlaví; Male; zvířata; infestace roztoči; prevalence